2006
DOI: 10.1002/art.22031
|View full text |Cite
|
Sign up to set email alerts
|

Anti–N‐methyl‐D‐aspartate receptor antibodies, cognitive dysfunction, and depression in systemic lupus erythematosus

Abstract: Range Achievement Test-3 (WRAT-3). Serum anti-NR2antibodies were measured by enzyme-linked immunosorbent assay using a pentapeptide from the human NMDA receptor.Results. Cognitive dysfunction was found in 28 of 60 patients (mild in 8, moderate in 20) before adjustment for WRAT-3 and in 35 of 60 patients (mild in 15, moderate in 11, and severe in 9) after adjustment for WRAT-3. The changes were most pronounced in the memory and visuospatial domains. There was no significant association between anti-NR2 antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
181
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(193 citation statements)
references
References 47 publications
9
181
0
1
Order By: Relevance
“…Omdal et al (19) reported an association between anti-NR2 antibodies and depressed mood as well as decreased short-term memory and learning. However, although there has been 1 additional report of an association with depression (44), 4 cross-sectional studies (20,(44)(45)(46) did not confirm these findings. In animal models, enhanced permeability of the bloodbrain barrier was a critical factor for anti-NR2 antibodies to enter the intrathecal space and gain access to neuronal cells (15).…”
Section: Discussionmentioning
confidence: 93%
“…Omdal et al (19) reported an association between anti-NR2 antibodies and depressed mood as well as decreased short-term memory and learning. However, although there has been 1 additional report of an association with depression (44), 4 cross-sectional studies (20,(44)(45)(46) did not confirm these findings. In animal models, enhanced permeability of the bloodbrain barrier was a critical factor for anti-NR2 antibodies to enter the intrathecal space and gain access to neuronal cells (15).…”
Section: Discussionmentioning
confidence: 93%
“…Anti-Nmethyl-D-aspartate receptor antibodies have been associated with neuropsychiatric symptoms in SLE, but their presence alone does not explain cognitive dysfunction, depression, or anxiety in patients with SLE [76]. Anti-NR2a antibodies may be associated with depressed mood but may not be associated with cognitive dysfunction in patients with SLE [77]. Anti-neuronal antibodies and abnormalities seen on SPECT scan appear to be useful in diagnosing CNS-SLE in pediatric patients [68].…”
Section: Rheumatic Disordersmentioning
confidence: 99%
“…Three further publications [57][58][59] were obtained from review of the reference lists of included articles.…”
Section: Literature Search Strategy and Articles Retrievedmentioning
confidence: 99%
“…Three further publications were obtained from review of the reference lists of included articles [57][58][59] . While one of those 59 showed and association between serum anti-NR2…”
Section: Anti-n-methyl-d-aspartate (Nmda) Receptor Antibodiesmentioning
confidence: 99%